MENJAGA ETIKA IKLAN PADA ERA DIGITAL : EKSPLOITASI AGAMA DALAM IKLAN DIGITAL MIRAS DI INSTAGRAM @MINUMANANAKMUDA - Fatimah; Syela Mutiara Zahra; Daniel Handoko (CV. Denasya Smart Publisher, 2025)
The development of digital technology has driven significant changes in advertising strategies in Indonesia. However, this transformation has also brought new challenges in maintaining ethical standards in marketing communications. This study aims to examine the extent to which the Indonesian Advertising Ethics (Etika Pariwara Indonesia/EPI) is applied in digital advertising practices. Using a qualitative approach and document analysis, this research analyzes several digital advertisements suspected of violating religious, ethical, and consumer protection principles, including honesty and social responsibility. The findings reveal that despite the existence of formal regulations, violations of EPI provisions still occur—particularly on digital platforms that are difficult to monitor directly. This study highlights the importance of strengthening regulations, educating industry players, and encouraging active public participation in monitoring advertising content. Thus, advertising ethics are expected to be preserved in an increasingly fast-paced and digital communication era.